#### Answer

$f^{-1}(x) = \sqrt[5] {\sqrt[7] y + 6 }$

#### Work Step by Step

$f(x) = (x^{5} - 6)^{7}$
$y = (x^{5} - 6)^{7}$
$\sqrt[7] y = x^{5} - 6$
$\sqrt[7] y + 6 = x^{5}$
$\sqrt[5] {\sqrt[7] y + 6 } = x$
$\sqrt[5] {\sqrt[7] y + 6 } = f^{-1}(x)$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$f^{-1}(x) = \sqrt[5] {\sqrt[7] y + 6 }$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.